Ternary positive electrode material, preparation method and electrochemical device
Patent Information
- Application Number
- CN202611406941.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-27
AI Technical Summary
然而,该高镍三元正极材料在高倍率应用场景下面临诸多挑战
1、本申请在制备正极材料时,通过在高镍三元正极材料基体颗粒表面依次形成包含铝酸锂的内层和包含磷酸钛铝锂的外层,且内层中的铝酸锂以非晶态或纳米晶-非晶复合结构的形式存在,使得该内层能够为基体提供界面保护并抑制界面副反应,同时为锂离子提供较为丰富的迁移路径,并且外层中的磷酸钛铝锂能够为锂离子提供快速的跨界面传输通道,由此,内层与外层相互配合,使正极材料在高倍率放电条件下能够保持较低的界面阻抗和较高的锂离子传输效率,从而兼顾高倍率性能与循环稳定性。
Smart Images

Figure CN122992045A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of new energy technology, and in particular to a ternary cathode material, its preparation method, and an electrochemical device. Background Technology
[0002] With the development of new energy technologies, higher requirements are being placed on the energy density, rate performance, and cycle life of lithium-ion batteries. High-nickel ternary cathode materials, due to their high specific capacity (up to 230 mAh / g or more), are considered an ideal choice for achieving high-energy-density power batteries. However, these high-nickel ternary cathode materials face numerous challenges in high-rate applications. During high-rate discharge, the alkaline lithium salts remaining on the material surface undergo side reactions with the electrolyte, generating a high-resistivity CEI film on the particle surface. This increases the interfacial impedance of the cathode material, thus affecting its rate performance. Furthermore, in a deeply delithiated state, the NCM material undergoes an H2→H3 phase transition, causing anisotropic shrinkage of its lattice volume. This leads to microcracks within the secondary particles, and the electrolyte penetrates along these cracks, further exacerbating the side reactions and accelerating capacity decay. Simultaneously, the insufficient lithium-ion transport rate at the particle interface also reduces usable capacity.
[0003] Therefore, how to improve the interface stability and lithium-ion transport rate of high-nickel ternary cathode materials while maintaining their high energy density advantage is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0004] In view of this, in order to solve at least one of the above technical problems, this application provides a method for preparing a ternary cathode material.
[0005] In addition, this application also provides a ternary cathode material prepared by the aforementioned preparation method and its application in the preparation of electrochemical devices.
[0006] In a first aspect, this application provides a method for preparing a ternary cathode material, comprising: adding an aluminum source dispersion dropwise to a dispersion containing a high-nickel ternary cathode material and mixing, then adding a lithium source and an aqueous solution containing a complexing agent and adjusting the pH to allow the aluminum source and the lithium source in the aluminum source dispersion to undergo a hydrolysis-condensation reaction on the surface of the high-nickel ternary cathode material to form a LiAlO2 precursor gel coating the surface of the high-nickel ternary cathode material, thereby obtaining a first precursor; mixing a titanium source, a phosphorus source, an aluminum source, a lithium source, and a solvent to form a lithium titanium aluminum phosphate precursor solution; and adding the lithium titanium aluminum phosphate precursor solution dropwise to the first precursor. The lithium titanium aluminum phosphate precursor is deposited on the surface of the first precursor to obtain a composite precursor; the solvent in the composite precursor is evaporated to a wet gel state and dried to obtain a dried composite precursor material; and B2O3 flux is added to the dried composite precursor material and sintered to form an inner coating layer of amorphous LiAlO2 / or an inner coating layer of a composite of amorphous LiAlO2 and nanocrystalline LiAlO2 in the LiAlO2 precursor, while the lithium titanium aluminum phosphate precursor forms an outer coating layer of crystalline lithium titanium aluminum phosphate under the action of the B2O3 flux, thereby obtaining the cathode material.
[0007] Based on the first aspect, in some embodiments of this application, during the sintering process, at the interface between the inner coating layer and the outer coating layer, at least one element between the amorphous LiAlO2 and the crystalline lithium titanium aluminum phosphate interdiffusion forms a concentration gradient region.
[0008] Based on the first aspect, in some embodiments of this application, the step of adding B2O3 flux to the composite precursor dry material and sintering includes: adding B2O3 flux to the composite precursor dry material and performing a first sintering, so that the LiAlO2 precursor forms amorphous LiAlO2 on the surface of the high-nickel ternary cathode material, obtaining a first sintered product; and performing a second sintering on the first sintered product, so that the amorphous LiAlO2 partially crystallizes to form nanocrystalline LiAlO2, forming an inner coating layer with a composite of amorphous LiAlO2 and nanocrystalline LiAlO2, while the lithium titanium aluminum phosphate precursor is converted into crystalline lithium titanium aluminum phosphate under the action of the B2O3 flux to form the outer coating layer, and under the conditions of the second sintering, at least one element between the amorphous LiAlO2 and the crystalline lithium titanium aluminum phosphate diffuses to form a concentration gradient region.
[0009] Based on the first aspect, in some embodiments of this application, the temperature of the first sintering is 350℃~450℃ and the time is 1h~3h; and / or, the temperature of the second sintering is 550℃~650℃ and the time is 2h~5h.
[0010] Based on the first aspect, in some embodiments of this application, the secondary sintering includes a first heat preservation process and a second heat preservation process, wherein the temperature of the first heat preservation process is lower than the temperature of the second heat preservation process, the temperature of the first heat preservation process is 550℃~620℃ and the time is 2h~5h, and the temperature of the second heat preservation process is 620℃~650℃ and the time is 1h~3h.
[0011] Based on the first aspect, in some embodiments of this application, the heating rate of the primary sintering is 3°C / min to 5°C / min; and / or, the heating rate of the secondary sintering is 3°C to 5°C.
[0012] Based on the first aspect, in some embodiments of this application, the chemical formula of the high-nickel ternary cathode material is LiNi. α Co β Mn 1-α-β O2, where 0.8≤α≤0.95, 0<β<0.2.
[0013] Based on the first aspect, in some embodiments of this application, the dropping rate of the aluminum source dispersion added to the dispersion containing the high-nickel ternary cathode material is 0.5 mL / min to 1 mL / min; and / or, the dropping rate of the lithium aluminum titanium phosphate precursor solution added to the first precursor is 0.1 mL / min to 10 mL / min.
[0014] Based on the first aspect, in some embodiments of this application, when preparing the lithium aluminum titanium phosphate precursor solution, the chemical formula LATP is used... 1.3 Al 0.3 Ti 1.7 The precursor solution was prepared by stoichiometric ratio of each element in (PO4)3. When preparing the lithium titanium aluminum phosphate precursor solution, a water-ethanol mixture with a volume ratio of 1:1 was used as the solvent.
[0015] Based on the first aspect, in some embodiments of this application, the total addition amount of the inner coating layer and the outer coating layer is 0.5wt% to 1.5wt% based on the mass of the high-nickel ternary cathode material; and / or, the mass ratio of the inner coating layer to the outer coating layer is 2:1 to 5:1.
[0016] Based on the first aspect, in some embodiments of this application, the amount of B2O3 flux added is 0.5% to 3% of the mass of the lithium titanium aluminum phosphate precursor.
[0017] Secondly, this application provides a cathode material, the cathode material comprising a substrate and an inner coating layer and an outer coating layer covering the outer surface of the substrate; the substrate material comprises a high-nickel ternary cathode material; the inner coating layer comprises amorphous LiAlO2 / or a composite structure of amorphous LiAlO2 and nanocrystalline LiAlO2; the outer coating layer comprises crystalline lithium titanium aluminum phosphate.
[0018] Based on the second aspect, in some embodiments of this application, at the interface between the inner coating layer and the outer coating layer, at least one element between the amorphous LiAlO2 and the crystalline lithium titanium aluminum phosphate diffuses to form a concentration gradient region.
[0019] Based on the second aspect, in some embodiments of this application, the mass ratio of the inner coating layer to the outer coating layer is 2:1 to 5:1; and / or, the total coating amount of the inner coating layer and the outer coating layer is 0.5wt% to 1.5wt% of the mass of the matrix material.
[0020] Thirdly, this application provides an electrochemical device including a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises a positive electrode material as described above.
[0021] The cathode material and its preparation method provided in this application involve sequentially coating the surface of a high-nickel cathode material matrix particles with an inner layer containing lithium aluminate and an outer layer containing lithium titanium aluminum phosphate. The lithium aluminate in the inner layer exists in an amorphous or nanocrystalline-amorphous composite structure, enabling the cathode material to exhibit higher interfacial stability and lithium-ion transport rate under high-rate discharge conditions. Furthermore, the lithium aluminate in the inner layer forms a physical barrier between the material and the electrolyte, reducing direct contact between the electrolyte and the matrix surface, thereby suppressing side reactions between the alkaline lithium salt and the electrolyte, and the resulting formation of a high-impedance CEI film, thus contributing to a reduction in interfacial impedance. The lithium titanium aluminum phosphate in the outer layer possesses three-dimensionally interconnected lithium-ion migration channels, providing a rapid pathway for lithium-ion migration from the bulk matrix to the electrolyte, thereby improving the efficiency of lithium-ion cross-interfacial transport and contributing to improved usable capacity utilization at high rates. Meanwhile, the disordered free volume and defects in the inner lithium aluminate amorphous structure can enrich the migration path of lithium ions, which is conducive to the conduction of lithium ions in the inner layer, thereby working with the outer layer to further improve the overall transport efficiency of lithium ions from the bulk phase to the interface.
[0022] Building upon this foundation, by sintering the inner LiAlO2 precursor to an amorphous state and crystallizing some of the amorphous LiAlO2 to form a nanocrystalline-amorphous composite structure, while simultaneously converting the outer LATP precursor into crystalline LATP, the high ion conductivity of the inner layer and the structural stability of the outer layer are maintained, thus balancing the rate performance and cycle life of the cathode material. Furthermore, since the lithium aluminate in the inner layer and the high-nickel ternary matrix share the same oxygen stacking mode, they can form a coherent or semi-coherent interface, which helps improve the bonding strength between the coating layer and the matrix. This reduces interface delamination and microcrack propagation caused by lattice volume shrinkage during cycling, contributing to extended battery cycle life. Therefore, this application enables the high-nickel ternary cathode material to maintain its high energy density advantage while exhibiting good interface stability and lithium-ion transport capability under high-rate discharge conditions. Attached Figure Description
[0023] Figure 1 A process flow diagram of the cathode material provided in this application.
[0024] Figure 2 This is an FESEM image of the high-nickel ternary cathode material after surface coating in Example 1 of this application.
[0025] Figure 3 This is the XRD pattern of the inner LiAlO2 layer in Embodiment 1 of this application.
[0026] Figure 4 This is the XRD pattern of the inner layer LiAlO2 in Example 9 (highly crystalline LiAlO2 group) of this application. Detailed Implementation
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the embodiments of this application pertain. The terminology used herein is for the purpose of describing particular implementations only and is not intended to limit the embodiments of this application. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0028] The following describes some embodiments of this application in detail. Unless otherwise specified, the embodiments and features described below can be combined with each other.
[0029] High-nickel ternary cathode materials suffer from poor interfacial stability, structural degradation, and insufficient lithium-ion transport rates in high-rate applications. To address these issues, researchers have explored various modification strategies, including doping, coating, and concentration gradients, but these approaches still struggle to balance high-rate performance with long-cycle stability.
[0030] For this purpose, please see Figure 1 This application provides a method for preparing a cathode material, comprising the following steps: Step S1: Add the aluminum source dispersion dropwise to the dispersion containing the high-nickel ternary cathode material and mix. Then add the lithium source and an aqueous solution containing a complexing agent and adjust the pH to allow the aluminum source and the lithium source in the aluminum source dispersion to undergo a hydrolysis-condensation reaction on the surface of the high-nickel ternary cathode material to form a LiAlO2 precursor gel coated on the surface of the high-nickel ternary cathode material, thus obtaining the first precursor.
[0031] By adding the aluminum source dispersion dropwise to the dispersion containing the high-nickel ternary cathode material, this dropwise addition helps to uniformly disperse the aluminum source in the liquid phase system, thereby achieving a more consistent concentration distribution of the aluminum source throughout the reaction system. This facilitates the smooth progress of the subsequent hydrolysis-condensation reaction. Simultaneously, the added complexing agent chelates metal ions at the molecular level, slowing down the hydrolysis-condensation reaction rate and contributing to the formation of a more complete LiAlO2 precursor gel network. Furthermore, adjusting the pH provides a suitable chemical environment for the hydrolysis-condensation reaction, allowing the LiAlO2 precursor gel to preferentially and uniformly nucleate and grow on the particle surface, contributing to complete coverage of the matrix particles by the LiAlO2 precursor gel. Thus, the LiAlO2 precursor gel can form a uniform, continuous, and dense LiAlO2 precursor gel coating layer on the surface of the high-nickel ternary cathode material, providing a favorable precursor distribution for obtaining an inner layer with good interfacial protection after subsequent sintering.
[0032] In some embodiments, in step S1, the general chemical formula of the high-nickel ternary cathode material is LiNi. α Co β Mn 1-α-β O2, where 0.8 ≤ α ≤ 0.95, 0 < β < 0.2. High-nickel ternary materials within this chemical formula range exhibit high specific capacity, which is beneficial for achieving high energy density.
[0033] In some embodiments, the median particle size D50 of the high-nickel ternary cathode material in step S1 is 5 μm to 14 μm. A suitable median particle size helps to balance the processing performance and electrochemical performance of the material.
[0034] In some embodiments, the solvent in the dispersion containing the high-nickel ternary cathode material in step S1 includes anhydrous ethanol. Anhydrous ethanol has low surface tension and good volatility, which helps to uniformly disperse the high-nickel ternary cathode material therein, and can be quickly removed during the subsequent drying process, reducing the impact of solvent residue on the quality of the coating layer.
[0035] In some embodiments, the solvent in the aluminum source dispersion includes anhydrous ethanol, which is used to dissolve the aluminum source and helps to uniformly disperse the aluminum source in the organic solvent and form a stable solution.
[0036] In some embodiments, the aluminum source in step S1 includes at least one of aluminum isopropoxide, aluminum nitrate, and aluminum sulfate. These aluminum sources have good solubility in anhydrous ethanol and can uniformly release aluminum ions to participate in subsequent hydrolysis-condensation reactions, thereby contributing to the formation of a uniformly composed LiAlO2 precursor gel network.
[0037] In some embodiments, the dropping rate of the aluminum source dispersion in step S1 when added to the dispersion containing the high-nickel ternary cathode material is 0.5 mL / min to 1 mL / min. This dropping rate helps to maintain a relatively stable concentration gradient of the aluminum source dispersion during the addition of the high-nickel ternary cathode material, thereby enabling a more uniform concentration distribution of the aluminum source in each local area, which in turn facilitates the formation of a uniform coating layer of the LiAlO2 precursor gel on the particle surface.
[0038] In some embodiments, the complexing agent in step S1 includes citric acid, which contains multiple carboxyl groups and can form chelates with metal ions in the solution, thereby chelating metal ions at the molecular level, slowing down the hydrolysis-condensation reaction rate, and helping to form a more complete LiAlO2 precursor gel network.
[0039] In some embodiments, the pH value in step S1 is 6.8 to 7.2, and dilute ammonia is used for pH adjustment. This pH value provides a suitable chemical environment for the hydrolysis-condensation reaction of the aluminum and lithium sources, which helps to promote the uniform nucleation and growth of the LiAlO2 precursor gel on the particle surface, thereby facilitating the obtaining of a uniform LiAlO2 precursor gel coating layer. The pH value can be, for example, 6.8, 6.9, 7.0, 7.1, 7.2, or any value within the range of any two of the above values.
[0040] Step S2: Mix the titanium source, phosphorus source, aluminum source, lithium source and solvent to form a lithium titanium aluminum phosphate precursor solution.
[0041] Mixing titanium, phosphorus, aluminum, lithium sources and solvents to form a lithium titanium aluminum phosphate precursor solution enables the components to achieve uniform mixing at the molecular level in the liquid phase. This facilitates the formation of a crystalline lithium titanium aluminum phosphate outer coating layer with a pure-phase NASICON structure during subsequent sintering. This NASICON structure has three-dimensional interconnected lithium ion migration channels, which helps to provide a fast transport path for lithium ions.
[0042] In some embodiments, the titanium source in step S2 includes at least one selected from tetrabutyl titanate, isopropyl titanate, tetraethyl titanate, and titanium tetrachloride. The above-mentioned titanium sources have good solubility in anhydrous ethanol and can uniformly release titanium ions to participate in the formation of the lithium aluminum titanium phosphate precursor, thereby helping to obtain a homogeneous lithium aluminum titanium phosphate precursor solution.
[0043] In some embodiments, the phosphorus source in step S2 includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, triethyl phosphate, and phosphorus pentoxide. The aforementioned phosphorus sources have good solubility or miscibility in solvents and can uniformly provide phosphate ions to participate in the formation of the lithium titanium aluminum phosphate precursor, thereby contributing to obtaining a homogeneous lithium titanium aluminum phosphate precursor solution.
[0044] In some embodiments, the aluminum source in step S2 includes at least one of aluminum nitrate, aluminum isopropoxide, aluminum phosphate, and boehmite. These aluminum sources have good solubility or dispersibility in solvents, enabling them to uniformly provide aluminum ions to participate in the formation of the lithium titanium aluminum phosphate precursor, thereby contributing to obtaining a homogeneous lithium titanium aluminum phosphate precursor solution.
[0045] In some embodiments, the lithium source in step S2 includes at least one selected from lithium nitrate, lithium acetate, lithium carbonate, lithium hydroxide, and lithium chloride. These lithium sources have good solubility in solvents and can uniformly provide lithium ions to participate in the formation of the lithium titanium aluminum phosphate precursor, thereby helping to obtain a homogeneous lithium titanium aluminum phosphate precursor solution.
[0046] In some embodiments, the solvent in step S2 includes anhydrous ethanol and deionized water. Anhydrous ethanol is used to dissolve the titanium source, which helps the titanium source to be uniformly dispersed in the organic solvent and form a stable solution; deionized water is used to dissolve the lithium source, aluminum source, and phosphorus source, which facilitates the full dissociation of each component and their participation in the formation of the lithium titanium aluminum phosphate precursor. This mixed solvent system composed of anhydrous ethanol and deionized water can simultaneously dissolve the titanium source, phosphorus source, aluminum source, and lithium source components, thereby helping to obtain a homogeneous lithium titanium aluminum phosphate precursor solution.
[0047] In some embodiments, when preparing the lithium aluminum titanium phosphate precursor solution, the LATP chemical formula Li 1.3 Al 0.3 Ti 1.7 The precursor solution was prepared by stoichiometric ratio of each element in (PO4)3. When preparing the lithium titanium aluminum phosphate precursor solution, a water-ethanol mixture with a volume ratio of 1:1 was used as the solvent.
[0048] When preparing the lithium titanium aluminum phosphate precursor solution according to the above molar ratio, the four elements Ti, P, Al and Li in the lithium titanium aluminum phosphate precursor solution can maintain a proportional relationship that matches the stoichiometric ratio of lithium titanium aluminum phosphate, which is conducive to the formation of lithium titanium aluminum phosphate with a pure phase NASICON structure in the subsequent sintering process and helps to obtain a stable fast ion conductor outer layer.
[0049] Step S3: Add the lithium titanium aluminum phosphate precursor solution dropwise to the first precursor, so that the lithium titanium aluminum phosphate precursor is deposited on the surface of the first precursor to obtain the composite precursor.
[0050] Introducing the lithium titanium aluminum phosphate precursor solution into the reaction system by dropwise helps to ensure that the precursor solution uniformly contacts and spreads on the surface of the first precursor coating material. This further forms a uniform outer layer of precursor covering the surface of the particles already coated with LiAlO2 precursor gel, resulting in a composite precursor coating material with a double-layer structure of inner LiAlO2 precursor gel and outer lithium titanium aluminum phosphate precursor. This provides a favorable precursor distribution state for obtaining a cathode material with a double-layer coating structure after subsequent sintering.
[0051] In some embodiments, in step S3, the dropping rate of the lithium titanium aluminum phosphate precursor solution when added to the first precursor is 0.1 mL / min to 10 mL / min. This dropping rate helps to maintain a relatively stable concentration change of the lithium titanium aluminum phosphate precursor solution during the addition process, thereby facilitating the uniform spreading of the lithium titanium aluminum phosphate precursor on the surface of the first precursor coating material. The dropping rate can be exemplarily 0.1 mL / min, 0.5 mL / min, 1 mL / min, 2 mL / min, 5 mL / min, 8 mL / min, 10 mL / min, or any value within the range of any two of the above values.
[0052] Step S4: Evaporate the solvent in the composite precursor to a wet gel state, and then dry it to obtain the dried composite precursor material.
[0053] In step S4, the solvent in the composite precursor is evaporated to a wet gel state and then dried. The solvent evaporation process allows the sol in the composite precursor to gradually concentrate and transform into a wet gel on the surface of the high-nickel ternary cathode material. This ensures that the LiAlO2 precursor and lithium aluminum titanium phosphate precursor maintain a good distribution on the surface of the matrix particles. At the same time, the drying process further removes residual solvent from the wet gel, thereby forming a structurally stable dry gel coating layer on the surface of the matrix particles. This is beneficial for maintaining the integrity and uniformity of the coating layer during the subsequent sintering process.
[0054] In some embodiments, the evaporation temperature in step S4 is 60°C to 100°C. This evaporation temperature allows the solvent in the composite precursor to evaporate smoothly, which helps the sol to gradually concentrate and transform into a wet gel on the surface of the matrix particles, thereby maintaining a good distribution of the LiAlO2 precursor and the lithium aluminum titanium phosphate precursor on the surface of the matrix particles. The evaporation temperature can, for example, be 70°C, 80°C, 90°C, or any value within the range of any two of the above values.
[0055] In some embodiments, the drying temperature in step S4 is 100°C to 150°C. This drying temperature can effectively remove residual solvent from the wet gel, allowing the composite precursor to form a structurally stable dry gel coating layer on the surface of the matrix particles. This is beneficial for maintaining the integrity and uniformity of the coating layer during subsequent sintering. The drying temperature can, for example, be 100°C, 120°C, 150°C, or any value within the range of any two of the above values.
[0056] Step S5: Add B2O3 flux to the dry composite precursor and sinter it to form an inner coating layer of amorphous LiAlO2 / or an inner coating layer of a composite of amorphous LiAlO2 and nanocrystalline LiAlO2. At the same time, the lithium titanium aluminum phosphate precursor forms an outer coating layer of crystalline lithium titanium aluminum phosphate under the action of B2O3 flux, thereby obtaining the cathode material.
[0057] In step S5, B2O3 flux is added to the dried composite precursor material and sintered. During the sintering process, the B2O3 flux can form a trace liquid phase, which helps to promote the migration and spreading of each component in the composite precursor on the surface of the matrix particles, thereby making the coating layer more uniform and densely distributed on the surface of the matrix particles. Simultaneously, this sintering process enables the LiAlO2 precursor to form an inner coating layer containing amorphous LiAlO2, or an inner coating layer containing a composite structure of amorphous LiAlO2 and nanocrystalline LiAlO2. The disordered free volume and defect sites in the amorphous structure provide abundant migration pathways for lithium ions, while the composite structure of amorphous and nanocrystalline forms can enhance the structural stability of the inner layer while retaining high ion conductivity. Furthermore, this sintering process can also transform the lithium titanium aluminum phosphate precursor into crystalline lithium titanium aluminum phosphate under the action of B2O3 flux, forming an outer coating layer with NASICON-type three-dimensional interconnected lithium ion migration channels. This outer coating layer can provide a rapid transport path for lithium ions to migrate from the bulk phase of the matrix to the electrolyte. Thus, a cathode material with the synergistic effect of inner layer interface protection and outer layer rapid ion conduction can be obtained through a single sintering process.
[0058] During the sintering process in step S5, at the interface between the inner and outer coating layers, at least one element between amorphous LiAlO2 and crystalline lithium titanium aluminum phosphate diffuses to form a concentration gradient region. The presence of this concentration gradient region helps to alleviate the lattice mismatch and interfacial stress between the inner and outer coating layers, thereby forming a relatively stable interfacial bonding state between the two coating layers. At the same time, this concentration gradient region can reduce the energy barrier for lithium ion migration across the interface between the inner and outer coating layers, which is beneficial to the continuous conduction of lithium ions between the inner and outer coating layers, thereby further improving the overall transport efficiency of lithium ions from the bulk matrix to the outer surface.
[0059] It should be noted that during this sintering process, at the interface between the inner and outer coating layers, the amorphous matrix in the amorphous LiAlO2, with its loose network structure and abundant free volume, provides a substrate for the Ti from the outer lithium aluminum titanium phosphate precursor. 4+ and PO4 3- It provides inward diffusion channels, allowing Ti and P elements to migrate from the outer layer to the shallow surface region of the inner amorphous LiAlO2, driven by the concentration gradient. Simultaneously, Al in the inner layer... 3+ The elements migrate outwards, creating a concentration gradient region of interdiffusion between the inner and outer coating layers. The nanocrystalline LiAlO2 already formed in the inner layer, due to its relatively complete lattice structure, largely does not participate in this interdiffusion, but it limits the excessive expansion of the concentration gradient region, thus preventing structural instability of the coating layer due to excessive interdiffusion. The existence of this concentration gradient region helps alleviate lattice mismatch and interfacial stress between the inner and outer coating layers, while also reducing the energy barrier for lithium-ion migration across the interface between them. This results in more continuous lithium-ion conduction between the inner and outer coating layers, enabling the cathode material to achieve both high-rate performance and cycle stability.
[0060] In some embodiments, in step S5, based on the mass of the high-nickel ternary cathode material, the total addition amount of the inner and outer coating layers is 0.5 wt% to 1.5 wt%. This total addition range allows for relatively complete coating coverage of the cathode material matrix particles, thereby helping to suppress direct contact between the electrolyte and the matrix surface and the resulting side reactions. Simultaneously, the moderate coating thickness helps to shorten the diffusion path of lithium ions within the coating layer, thus contributing to a balance between interface stability and lithium ion transport efficiency.
[0061] In some embodiments, in step S5, the mass ratio of the inner coating layer to the outer coating layer is 2:1 to 5:1. Within this mass ratio range, the inner coating layer has sufficient thickness to form a relatively complete coverage of the substrate surface, and the outer coating layer can form a continuous lithium-ion transport channel. This allows the interface protection function of the inner layer and the rapid ion conduction function of the outer layer to be better synergistically utilized, which helps to balance the rate performance and cycle stability of the cathode material.
[0062] In some embodiments, in step S5, the amount of B2O3 flux added is 0.5% to 3% of the mass of the lithium titanium aluminum phosphate precursor. Within this range, B2O3 can form a suitable amount of trace liquid phase during sintering. This trace liquid phase helps promote the migration and rearrangement of the components in the composite precursor on the particle surface, thereby enabling the LATP precursor to form a uniform phase and spread at a lower temperature, which is beneficial for forming a structurally complete outer coating layer. The exemplary amount of B2O3 flux added can be 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 2.0%, 2.5%, 3.0%, or any value within the range of any two of the above values.
[0063] In step S5, the step of adding B2O3 flux to the dried composite precursor material and sintering it includes: Step 1: Add B2O3 flux to the composite precursor dry material and perform a first sintering to form amorphous LiAlO2 on the surface of the high-nickel ternary cathode material, thus obtaining the first sintered product.
[0064] In step 1, B2O3, acting as a flux, forms a trace liquid phase during the primary sintering process. This trace liquid phase facilitates the migration and rearrangement of the components in the composite precursor on the particle surface, thereby improving the uniformity and density of the coating layer on the matrix particle surface. Simultaneously, this primary sintering allows for the complete decomposition and removal of organic components in the LiAlO2 precursor, resulting in the formation of LiAlO2 in an amorphous state on the particle surface. The disordered free volume and defect sites present in this amorphous LiAlO2 provide abundant migration pathways for lithium ions, thus enhancing the lithium ion conductivity in the inner layer. Furthermore, this amorphous LiAlO2, as the inner layer's existing form, provides the structural basis for the partial crystallization to form a nanocrystalline-amorphous composite structure during the subsequent secondary sintering, contributing to the final acquisition of an inner coating layer with both high lithium ion conductivity and good structural stability.
[0065] In some embodiments, in step 1, the sintering temperature is 350°C to 450°C, and the time is 1 hour to 3 hours. This sintering temperature and time help to fully decompose and remove the organic components in the composite precursor, and enable the LiAlO2 precursor to form amorphous LiAlO2 on the surface of the high-nickel ternary cathode material, thereby facilitating the retention of the amorphous structure to maintain its high lithium-ion conductivity. The sintering temperature can, for example, be 350°C, 370°C, 400°C, 420°C, 450°C, or any value within the range of any two of the above values; the sintering time can, for example, be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, or any value within the range of any two of the above values.
[0066] In some embodiments, the heating rate for a single sintering step is 3°C to 5°C / min. This heating rate helps maintain a relatively uniform temperature field distribution during sintering, ensuring that the components of the composite precursor are heated uniformly during the heating process, which is beneficial for the uniform and dense formation of the coating layer on the particle surface. Exemplary heating rates may be 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, or any value within the range of any two of the above values.
[0067] Step 2: The first sintering product is subjected to secondary sintering to partially crystallize amorphous LiAlO2 to form nanocrystalline LiAlO2, forming an inner coating layer composed of amorphous LiAlO2 and nanocrystalline LiAlO2. At the same time, the lithium titanium aluminum phosphate precursor is transformed into crystalline lithium titanium aluminum phosphate under the action of B2O3 flux to form an outer coating layer. Under the secondary sintering conditions, at least one element between amorphous LiAlO2 and crystalline lithium titanium aluminum phosphate diffuses to form a concentration gradient region.
[0068] During the secondary sintering process, the nanocrystalline-amorphous composite structure formed by the partial crystallization of amorphous LiAlO2 allows the inner layer to retain the abundant lithium-ion migration pathways of the amorphous state while gaining support from the nanocrystalline region, thus improving the structural stability of the inner layer. Simultaneously, the lithium titanium aluminum phosphate precursor is transformed into crystalline lithium titanium aluminum phosphate under the action of B2O3 flux. This crystalline lithium titanium aluminum phosphate possesses NASICON-type three-dimensional interconnected lithium-ion migration channels, providing a rapid transport path for lithium ions to migrate from the bulk phase of the matrix to the electrolyte, thereby improving ion conduction efficiency at high rates. Furthermore, the concentration gradient region formed by the interdiffusion of elements between amorphous LiAlO2 and crystalline lithium titanium aluminum phosphate helps alleviate interfacial stress between the inner and outer layers, reducing interfacial impedance, thus facilitating cross-interfacial migration of lithium ions between the inner and outer layers. Therefore, this cathode material achieves a balance between high-rate performance and cycle life through the synergistic effect of the inner layer providing interfacial protection and lithium-ion conduction, the outer layer providing a rapid lithium-ion transport channel, and the gradient region providing a low-impedance cross-interfacial migration path.
[0069] In some embodiments, in step 2, the secondary sintering temperature is 550℃~650℃, and the time is 2h~5h. This secondary sintering temperature and time can cause partial crystallization of amorphous LiAlO2, thereby forming a composite structure composed of amorphous and nanocrystalline states. This allows the inner layer to retain the rich lithium-ion migration pathways of the amorphous state while gaining support from the nanocrystalline region, which is beneficial to improving the structural stability of the inner layer. At the same time, this temperature and time condition can fully convert the lithium titanium aluminum phosphate precursor into crystalline lithium titanium aluminum phosphate under the action of B2O3 flux, allowing the outer layer to obtain NASICON-type three-dimensional interconnected lithium-ion migration channels, which is beneficial to improving the cross-interface transport efficiency of lithium ions. In addition, this temperature and time condition also helps to promote the interdiffusion of elements between amorphous LiAlO2 and crystalline lithium titanium aluminum phosphate, thereby forming a concentration gradient region, which is beneficial to relieving the interfacial stress between the inner and outer layers and reducing the interfacial impedance. The secondary sintering temperature can be, for example, 550℃, 570℃, 600℃, 620℃, 650℃ or any value within the range of any two of the above values; the secondary sintering time can be, for example, 2h, 2.5h, 3h, 4h, 5h or any value within the range of any two of the above values.
[0070] It should be noted that the secondary sintering includes a first holding process and a second holding process, wherein the temperature of the first holding process is lower than that of the second holding process. The temperature of the first holding process is 550℃~620℃, and the time is 2h~5h, while the temperature of the second holding process is 620℃~650℃, and the time is 1h~3h.
[0071] The temperature of the first stage of the heat treatment process is used to partially nanocrystallize the amorphous LiAlO2 to form a nanocrystalline-amorphous composite structure. The temperature of the second stage of the heat treatment process is used to convert the LATP precursor into crystalline LATP under the action of B2O3 flux. In this secondary sintering, the first stage of heat treatment is carried out at a lower temperature to obtain the nanocrystalline-amorphous composite structure of the inner LiAlO2, and then the second stage of heat treatment is carried out at a higher temperature to fully form the outer LATP phase. This segmented heat treatment setting helps to separately control the crystallinity of the inner layer and the degree of phase formation of the outer layer in the same secondary sintering process, thereby taking into account both the high ion conductivity of the inner layer and the structural stability of the outer layer.
[0072] In some embodiments, the heating rate for the secondary sintering is 3°C to 5°C. This heating rate helps to maintain a relatively uniform temperature field distribution during the secondary sintering process, thereby ensuring that the components of the first sintered product are heated uniformly during the heating process, which is beneficial to the uniform evolution of the coating layer structure and the uniform formation of crystalline lithium titanium aluminum phosphate. The heating rate can be exemplarily 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, or any value within the range of any two of the above values.
[0073] This application also provides a cathode material, comprising a substrate and an inner and outer coating layer covering the outer surface of the substrate; the substrate material comprises a high-nickel ternary cathode material; the inner coating layer comprises amorphous LiAlO2 / or a composite structure of amorphous LiAlO2 and nanocrystalline LiAlO2; the outer coating layer comprises crystalline lithium titanium aluminum phosphate. In this cathode material, the amorphous LiAlO2 in the inner coating layer can provide interfacial protection for the substrate material, suppressing side reactions between the electrolyte and the substrate surface. Simultaneously, the disordered free volume and defect sites in its amorphous structure can provide relatively abundant migration paths for lithium ions, thereby facilitating lithium ion conduction in the inner coating layer; the crystalline lithium titanium aluminum phosphate in the outer coating layer has NASICON-type three-dimensional interconnected lithium ion migration channels, providing a rapid transport path for lithium ions to migrate from the bulk phase of the substrate to the electrolyte. Thus, the inner and outer coating layers work together to enable the cathode material to maintain low interfacial impedance and high lithium-ion transport efficiency under high-rate discharge conditions.
[0074] In some embodiments, at the interface between the inner and outer coating layers, at least one element between amorphous LiAlO2 and crystalline lithium titanium aluminum phosphate interdiffusion forms a concentration gradient region. The presence of this concentration gradient region helps alleviate lattice mismatch and interfacial stress between the inner and outer coating layers, thereby creating a more stable interfacial bonding state between the two coating layers. Simultaneously, this concentration gradient region lowers the energy barrier for lithium ion migration across the interface between the inner and outer coating layers, thus facilitating continuous lithium ion conduction between them.
[0075] In some embodiments, the mass ratio of the inner coating layer to the outer coating layer is 2:1 to 5:1. Within this mass ratio range, the inner coating layer has sufficient thickness to form a relatively complete coverage of the substrate surface, and the outer coating layer can form a continuous lithium-ion transport channel. This allows the interface protection function of the inner layer and the rapid ion conduction function of the outer layer to be better synergistically utilized, which helps to balance the rate performance and cycle stability of the cathode material.
[0076] In some embodiments, the total coating amount of the inner and outer coating layers is 0.5 wt% to 1.5 wt% of the matrix material mass. This total coating amount range allows for relatively complete coating coverage of the matrix material particles, thereby helping to suppress direct contact between the electrolyte and the matrix surface and the resulting side reactions. Simultaneously, the moderate coating thickness helps to shorten the diffusion path of lithium ions within the coating layer, thus contributing to a balance between interface stability and lithium ion transport efficiency.
[0077] Compared with related technologies, the method for preparing the cathode material and the cathode material provided in this application have the following beneficial effects: 1. In the preparation of the cathode material, this application sequentially forms an inner layer containing lithium aluminate and an outer layer containing lithium titanium aluminum phosphate on the surface of the high-nickel ternary cathode material matrix particles. The lithium aluminate in the inner layer exists in the form of an amorphous state or a nanocrystalline-amorphous composite structure, which enables the inner layer to provide interfacial protection for the matrix and suppress interfacial side reactions, while providing a relatively rich migration path for lithium ions. The lithium titanium aluminum phosphate in the outer layer can provide a fast cross-interfacial transport channel for lithium ions. Thus, the inner and outer layers work together to enable the cathode material to maintain a low interfacial impedance and a high lithium ion transport efficiency under high-rate discharge conditions, thereby balancing high-rate performance and cycle stability.
[0078] 2. In preparing the cathode material, this application uses a sol-gel method to in-situ coat the LiAlO2 precursor gel onto the surface of the high-nickel ternary cathode material, and uses a segmented sintering process to control the crystallization state of the inner LiAlO2 layer (first sintering forms an amorphous state, and second sintering partially crystallizes to form a nanocrystalline-amorphous composite structure). This not only preserves the rich lithium-ion migration pathways in the amorphous structure, but also improves the structural stability of the inner layer through the support of the nanocrystalline region, so that the inner layer can maintain a high lithium-ion conductivity and interface protection effect during long-term cycling.
[0079] 3. In the preparation of the cathode material, this application adds B2O3 flux to the outer precursor, enabling the lithium titanium aluminum phosphate precursor to be converted into crystalline lithium titanium aluminum phosphate at a lower temperature and obtain NASICON-type three-dimensional interconnected lithium-ion migration channels. This provides a fast transport path for lithium-ion migration from the bulk matrix to the electrolyte. The lower sintering temperature helps to avoid damage to the high-nickel ternary matrix structure due to excessive temperature. In addition, the flux forms a trace liquid phase during sintering to promote LATP phase formation and spreading.
[0080] 4. In the preparation of the cathode material, this application allows elemental interdiffusion between the inner amorphous LiAlO2 and the outer crystalline lithium titanium aluminum phosphate during the secondary sintering process, thereby forming a concentration gradient region. The existence of this concentration gradient region helps to alleviate the interfacial stress between the inner and outer layers and reduce the interfacial impedance, which is conducive to the cross-interfacial migration of lithium ions between the inner and outer layers. In addition, in conjunction with the functions of the inner and outer layers, the overall lithium ion transport efficiency at high rates is improved.
[0081] This application also provides an electrochemical device including a positive electrode, a negative electrode, and an electrolyte disposed between the positive and negative electrodes. The positive electrode includes a positive electrode material as described above. Because the positive electrode contains the aforementioned positive electrode material, the electrochemical device can balance rate performance and cycle stability under high-rate discharge conditions.
[0082] The present application will be further described below with reference to specific embodiments and comparative examples.
[0083] Example 1 Step 1: NCM matrix dispersion: Take 5.0g LiNi 0.9 Co 0.05 Mn 0.05 O2 powder (i.e., high-nickel ternary cathode material, with a median particle size D50 of 6 μm) was added to 50 mL of anhydrous ethanol and ultrasonically dispersed for 30 min (frequency 40 kHz) to obtain suspension A.
[0084] Step 2.1: Inner LiAlO2 precursor coating: Weigh 0.098g of aluminum isopropoxide and dissolve it in 10mL of anhydrous ethanol to obtain solution B. The amount of aluminum isopropoxide added can form about 0.075g of LiAlO2, which is 0.75wt% of the inner LiAlO2 in the high-nickel ternary cathode material (5.0g).
[0085] Step 2.2: Weigh 0.11g of lithium acetate dihydrate and 0.38g of citric acid and dissolve them in 10mL of deionized water to obtain solution C. The amount of lithium acetate dihydrate added makes the molar ratio of Li to Al approximately 1.05.
[0086] Step 2.3: Under stirring at a frequency of 400 rpm, solution B is added dropwise (1.5 mL / min) to suspension A obtained in step 1. Then, solution C is added dropwise to the above mixture. The pH is adjusted to 7.0 with dilute ammonia. Stirring is continued for 1 h (stirring frequency of 400 rpm) to allow the aluminum source and lithium source to undergo hydrolysis-condensation reaction to form LiAlO2 precursor. The LiAlO2 precursor is then coated on the surface of the high-nickel ternary cathode material in gel form to obtain the first precursor coating material.
[0087] Step 3, Outer LATP Precursor Coating: The outer LATP layer is prepared according to a mass percentage of 0.25 wt% of the high-nickel ternary cathode material (5.0 g), meaning the theoretical amount of LATP precursor generated is approximately 0.0125 g. Specifically, 0.018 g of lithium nitrate, 0.014 g of aluminum nitrate, and 0.017 g of ammonium dihydrogen phosphate are dissolved in 5 mL of deionized water, and 0.08 g of citric acid is added to obtain solution D; 0.030 g of tetrabutyl titanate is dissolved in 5 mL of anhydrous ethanol to obtain solution E. Under stirring (stirring frequency of 300 rpm), solution D is first added to the first precursor coating material obtained in step 2.3, and then solution E is added dropwise (dropping rate of approximately 1 mL / min), maintaining a stirring speed of 350 rpm, so that the lithium aluminum titanium phosphate precursor is evenly spread on the surface of the first precursor coating material. After the addition is complete, stirring is continued for 1 h (stirring frequency of 300 rpm) to obtain the composite precursor coating material.
[0088] Step 4: Drying and Flux Addition: The composite precursor coating material obtained in Step 3 was stirred and evaporated in an 80°C water bath until it reached a wet gel state. It was then transferred to a forced-air drying oven and dried at 120°C for 12 hours to obtain the dried composite precursor material. 0.0015 g of B2O3 (approximately 1.2% of the outer LATP precursor mass) was added to this dried composite precursor material and gently ground to mix thoroughly.
[0089] Step 5: Segmented calcination: The material obtained in Step 4 is placed in a box furnace and heated to 400°C at a rate of 5°C / min for 2 hours under a flowing high-purity oxygen atmosphere (oxygen concentration > 99.5%) to allow for the thermal decomposition and removal of organic matter such as citric acid. Then, the temperature is increased to 600°C at a rate of 5°C / min for 4 hours to allow the inner LiAlO2 layer to undergo nanocrystallization. Finally, the temperature is increased to 650°C at a rate of 5°C / min for 1 hour to allow the outer LATP layer to crystallize. After sintering, the material is allowed to cool naturally in the furnace and passed through a 400-mesh sieve to obtain a high-nickel ternary cathode material with a bicomponent fast ion conductor layer coated on the surface. The total coating weight is 1.0 wt%, and the mass ratio of the inner LiAlO2 layer to the outer LATP layer is 3:1.
[0090] Example 2 The difference between this embodiment and Embodiment 1 is that in step 2.1, the inner layer LiAlO2 is adjusted to 0.67wt% based on the mass of the high-nickel ternary cathode material, and the amount of lithium acetate dihydrate is adjusted accordingly.
[0091] In step 3, the outer LATP layer is adjusted to 0.33 wt% based on the mass of the high-nickel ternary cathode material, and the amounts of each raw material are adjusted accordingly. The other steps are the same as in Example 1, resulting in a cathode material with a total coating amount of 1.0 wt% and a mass ratio of inner LiAlO2 to outer LATP of 2:1.
[0092] Example 3 The difference between this embodiment and Embodiment 1 is that in step 2.1, the inner layer LiAlO2 is adjusted to 0.80wt% based on the mass of the high-nickel ternary cathode material, and the amount of lithium acetate dihydrate is adjusted accordingly.
[0093] In step 3, the outer LATP layer is adjusted to 0.20 wt% based on the mass of the high-nickel ternary cathode material, and the amounts of each raw material are adjusted accordingly. The other steps are the same as in Example 1, resulting in a cathode material with a total coating amount of 1.0 wt% and a mass ratio of inner LiAlO2 to outer LATP of 4:1.
[0094] Example 4 The difference between this embodiment and Embodiment 1 is that in step 2.1, the inner layer LiAlO2 is adjusted to 0.375wt% based on the mass of the high-nickel ternary cathode material, and the amount of lithium acetate dihydrate is adjusted accordingly.
[0095] In step 3, the outer LATP layer is adjusted to 0.125 wt% based on the mass of the high-nickel ternary cathode material, and the amounts of each raw material are adjusted accordingly. The other steps are the same as in Example 1, resulting in a cathode material with a total coating amount of 0.5 wt% and a mass ratio of inner LiAlO2 to outer LATP of 3:1.
[0096] Example 5 The difference between this embodiment and Embodiment 1 is that in step 2.1, the inner layer LiAlO2 is adjusted to 1.125wt% based on the mass of the high-nickel ternary cathode material, and the amount of lithium acetate dihydrate is adjusted accordingly.
[0097] In step 3, the outer LATP layer is adjusted to 0.375 wt% based on the mass of the high-nickel ternary cathode material, and the amounts of each raw material are adjusted accordingly. The other steps are the same as in Example 1, resulting in a cathode material with a total coating amount of 1.5 wt% and a mass ratio of inner LiAlO2 to outer LATP of 3:1.
[0098] Example 6 The difference between this embodiment and Embodiment 1 is that in step 2.1, the inner layer LiAlO2 is adjusted to 0.83wt% based on the mass of the high-nickel ternary cathode material, and the amount of lithium acetate dihydrate is adjusted accordingly.
[0099] In step 3, the outer LATP layer is adjusted to 0.17 wt% based on the mass of the high-nickel ternary cathode material, and the amounts of each raw material are adjusted accordingly. The other steps are the same as in Example 1, resulting in a cathode material with a total coating amount of 1.0 wt% and a mass ratio of inner LiAlO2 to outer LATP of 5:1.
[0100] Example 7 The difference between this embodiment and Embodiment 1 is that in step 2.1, the inner layer LiAlO2 is adjusted to 0.50wt% based on the mass of the high-nickel ternary cathode material, and the amount of lithium acetate dihydrate is adjusted accordingly.
[0101] In step 3, the outer LATP layer is adjusted to 0.50 wt% based on the mass of the high-nickel ternary cathode material, and the amounts of each raw material are adjusted accordingly. That is, the total coating amount is 1.0 wt%, the mass ratio of the inner layer to the outer layer is 1:1, and the remaining steps are the same as in Example 1.
[0102] Example 8 The difference between this embodiment and Embodiment 1 is that in step 2.1, the inner layer LiAlO2 is adjusted to 2.25wt% based on the mass of the high-nickel ternary cathode material, and the amount of lithium acetate dihydrate is adjusted accordingly.
[0103] In step 3, the outer LATP layer is adjusted to 0.75 wt% based on the mass of the high-nickel ternary cathode material, and the amount of each raw material is increased accordingly. That is, the total coating amount is 3.0 wt%, the mass ratio of the inner layer to the outer layer is 3:1, and the remaining steps are the same as in Example 1.
[0104] Example 9 The difference between this embodiment and Embodiment 1 is that the segmented calcination process in step 5 is adjusted to be: after the first stage of holding at 400°C for 2 hours, the temperature is directly raised to 750°C for the second stage of holding for 4 hours, without the third stage of holding at 650°C. The remaining steps are the same as in Embodiment 1.
[0105] Example 10 The difference between this embodiment and Embodiment 1 is that in step 2.1, the inner layer LiAlO2 is adjusted to 0.225wt% based on the mass of the high-nickel ternary cathode material, and the amount of lithium acetate dihydrate is adjusted accordingly.
[0106] In step 3, the outer LATP layer is adjusted to 0.075 wt% based on the mass of the high-nickel ternary cathode material, and the amounts of each raw material are adjusted accordingly. That is, the total coating amount is 0.3 wt%, the mass ratio of the inner layer to the outer layer is 3:1, and the remaining steps are the same as in Example 1.
[0107] Comparative Example 1 This comparative example directly uses LiNi 0.9 Co 0.05 Mn 0.05 O2 powder is used as the positive electrode material and is not coated.
[0108] Comparative Example 2 The difference between this comparative example and Example 1 is that this comparative example does not perform the outer LATP precursor coating in step 3, but only prepares the inner LiAlO2 coating layer according to steps 2.1 to 2.3 of Example 1, wherein the coating amount of LiAlO2 is 1.0 wt% based on the mass of the high-nickel ternary cathode material.
[0109] In step 5, the segmented calcination only involves a first stage of holding at 400°C for 2 hours and a second stage of holding at 600°C for 4 hours, without a third stage of holding at 650°C. The entire process is carried out in an oxygen atmosphere.
[0110] Comparative Example 3 The difference between this comparative example and Example 1 is that this comparative example does not perform the inner layer LiAlO2 precursor coating in steps 2.1 to 2.3. Instead, the LATP precursor solution from step 3 is directly added to the NCM suspension obtained in step 1 to perform monolayer LATP coating. The coating amount of LATP is 1.0 wt% based on the mass of the high-nickel ternary cathode material, and B2O3 flux is added.
[0111] In step 5, the segmented calcination only involves a first stage of holding at 400°C for 2 hours and a second stage of holding at 600°C for 4 hours, without a third stage of holding at 650°C. The entire process is carried out in an oxygen atmosphere.
[0112] Comparative Example 4 The difference between this comparative example and Example 1 is that B2O3 flux is not added in step 4, while the remaining steps are the same as in Example 1.
[0113] The high-nickel ternary cathode materials with a surface coated with a bicomponent fast ion conductor layer prepared in the above embodiments and comparative examples were tested as follows: FESEM test: Field emission scanning electron microscope was used with an accelerating voltage of 2kV to observe the surface morphology of sample particles in secondary electron imaging mode.
[0114] XRD Testing: Qualitative analysis of the crystal structure of the sample materials was performed using an X-ray diffractometer (model: Ultima IV). CuKα rays (λ=1.5406Å) were used to perform XRD tests on each sample within the range of 10°–80° (2θ) at a scan rate of 1° / min. To confirm the crystallinity of the coating layer, LiAlO2 powder samples were also prepared separately using the exact same process conditions as the coating layer for testing.
[0115] Preparation of button cells: NCM ternary active material, SP, and PVDF were added sequentially in a ratio of 90.0:5.0:5.0. The mixture was stirred at 1800 rpm for 1.5 hours to ensure uniform mixing. Aluminum foil was prepared, and the slurry was poured into a mixing tank. After confirming the areal density through a test coating, the foil was coated onto the substrate and cold-pressed until the compacted density reached 2.9~3.1 g / cm³. 3 The coated electrode was baked at 110℃ for 10 hours; sliced using a 13.6mm slicer, and the sliced electrode was dried in a vacuum drying oven for 2 hours to obtain the positive electrode.
[0116] Place the positive electrode sheet inside the aluminum shell and add 5-6 drops of electrolyte (LBC3045M10); place the separator flat on the positive electrode sheet and add 2 drops of electrolyte; then stack the lithium sheet and nickel foam in sequence, add 6-7 drops of electrolyte, and cover with the negative electrode cap to prepare a coin cell.
[0117] Charge / discharge test: Place the assembled button cell battery in a constant temperature chamber. The test temperature should be 25±1℃, the ambient temperature should be 25±5℃, and the humidity should be <50%. The test voltage range is 2.8~4.3V, and the charge / discharge test is conducted using a 0.1C charging and 0.1C discharging method.
[0118] Rate performance test: During the rate performance test, the battery is first charged and discharged at a rate of 0.1C, and the 0.1C discharge capacity is recorded as the baseline capacity. Then, the battery is continuously discharged at 3C and 5C rates respectively, and the 3C and 5C discharge capacities are recorded. The percentage of 3C discharge capacity to 0.1C discharge capacity (i.e., 3C retention rate) and the percentage of 5C discharge capacity to 0.1C discharge capacity (i.e., 5C retention rate) are calculated respectively. 10C pulse retention rate (%, 10s): 10C continuous discharge for 10s, followed by a 30s interval cycle, and the capacity retention rate before the cutoff voltage is recorded.
[0119] 1C / 50-cycle retention rate (%): After two cycles of 0.1C charge-discharge, a 50-cycle test is performed at a 1C / 1C ratio.
[0120] The test results of the examples and comparative examples are shown in Table 1 below.
[0121] Table 1 Results Analysis: Comparing Example 1 with Comparative Examples 2 (monolayer LiAlO2 coating) and 3 (monolayer LATP coating), Example 1 outperformed the two comparative examples in both 5C retention rate (89.2%) and 10C pulse retention rate (84.5%), and its 50-cycle retention rate (95.8%) was also higher. Figure 2 The FESEM images shown reveal that the surface of the particles after double-layer coating is smooth and clean, with no exposed areas or isolated coated particles. This indicates that the composite coating layer is uniformly, continuously, and densely coated on the surface of the substrate particles. This demonstrates that the double-layer structure design of this application, which provides interfacial chemical protection through an inner LiAlO2 layer and a fast lithium-ion channel through an outer LATP layer, can simultaneously improve interfacial stability and lithium-ion transport rate based on a single material.
[0122] Furthermore, comparing Examples 1 (3:1), 2 (2:1), 3 (4:1), 6 (5:1), and 7 (1:1), it is evident that when the ratio of the inner to outer layer is 3:1, the 5C and 10C pulse retention rates and cycle retention rates are both optimal. This indicates that the inner layer has sufficient thickness at this ratio to ensure the integrity of the interface protection, while the outer layer can form continuous fast ion channels to exert its rapid conduction effect. When the ratio is controlled within the range of 3:1 to 4:1, the inner layer thickness is sufficient to prevent the electrolyte from penetrating into the substrate surface, allowing the synergistic effect of the double-layer protection to be fully realized. Simultaneously, the continuity of the outer LATP layer coverage is also good, effectively providing a rapid cross-interface transport channel for lithium ions, resulting in superior overall performance. Conversely, when the ratio leans towards 2:1 or 1:1 (i.e., the proportion of the outer layer increases relatively), the cycle retention rate decreases (86.5% in Example 7), indicating that the interface protection effect is somewhat affected after the inner layer is relatively thinned. When the ratio is biased towards 5:1 (i.e., the outer layer accounts for a relatively smaller proportion, as in Example 6), the 10C pulse retention rate is 79.0%, indicating that the continuity of the outer layer coverage is insufficient, and its contribution to the rapid transport of lithium ions is relatively limited. Based on the above comparison, it can be seen that the overall performance is better when the mass ratio of the inner layer to the outer layer is 3:1 to 4:1.
[0123] Furthermore, a comparison of Examples 1 (1.0 wt%), 4 (0.5 wt%), and 5 (1.5 wt%) with Examples 8 (3.0 wt%) and 10 (0.3 wt%) shows that the performance is excellent when the total coating amount is in the range of 0.5–1.5 wt%, with 1.0 wt% showing the best overall effect. Example 10 (0.3 wt%), even with a lower coating amount, still exhibits better 5C retention (72.5%) and 10C pulse retention (66.3%) than the uncoated Comparative Example 1 (62.3% and 55.8%), indicating that even with a lower coating amount, the double-layer coating structure of this application still provides certain interface protection and rate performance improvement to the substrate. When the total coating amount is increased to above 0.5 wt%, the coating layer provides more complete coverage of the substrate surface, further improving the overall performance. Example 8 (3.0 wt%) maintained good cycle stability even with a higher coating amount, but its initial capacity was adjusted at higher coating amounts (216.9 mAh / g). In terms of rate performance, a moderate coating thickness is more conducive to the rapid diffusion of lithium ions. Therefore, a total coating amount in the range of 0.5–1.5 wt% can effectively balance interface protection and ion transport efficiency.
[0124] Furthermore, comparing Example 1 (amorphous LiAlO2) with Example 9 (highly crystalline LiAlO2 at 750°C), it can be seen that, under the same ratio and total coating amount, Example 1 has higher 5C retention rate (89.2%) and 10C pulse retention rate (84.5%). Figure 3 and Figure 4 The XRD patterns shown indicate that the inner LiAlO2 in Example 1 exhibits typical amorphous diffuse scattering characteristics in the 2θ = 20°~30° range, confirming its existence as an amorphous or nanocrystalline-amorphous composite structure. In contrast, Example 9 shows sharp diffraction peaks, corresponding to highly crystalline γ-phase LiAlO2. This suggests that the excessively high calcination temperature (750°C) in Example 9 caused the inner LiAlO2 to completely transform from an amorphous state to a highly crystalline state. The amorphous LiAlO2 inner layer has higher ionic conductivity, which is beneficial for improving lithium-ion transport efficiency at high rates. However, the high calcination temperature may also cause thermal damage to the high-nickel ternary matrix structure, thus affecting electrochemical performance. Therefore, controlling the secondary sintering temperature within an appropriate range (e.g., 550~650°C) to maintain the amorphous or nanocrystalline-amorphous composite structure of the inner LiAlO2 is beneficial for obtaining excellent high-rate performance.
[0125] Furthermore, a comparison between Example 1 and Comparative Example 4 shows that, at the same calcination temperature, the B2O3 flux introduced in Example 1 can form a trace liquid phase during calcination. This trace liquid phase utilizes a liquid-phase-assisted mass transfer mechanism to promote the diffusion and reaction of the components of the LATP precursor, thereby facilitating the full phase formation of LATP at a relatively low temperature. Comparative Example 4, without the addition of B2O3, has a lower 10C pulse retention rate (78.5%) than Example 1 (84.5%), indicating that the addition of B2O3 helps to enhance the fast ion conductor function of the outer layer of LATP. Simultaneously, the 50-cycle retention rate of Comparative Example 4 (88.4%) is also lower than that of Example 1 (95.8%), demonstrating that after the B2O3 flux promotes the full phase formation of LATP, the integrity of the outer layer structure has a positive effect on improving rate performance and cycle stability.
[0126] In summary, the preparation method provided in this application sequentially forms an inner precursor gel containing LiAlO2 and an outer precursor containing LATP on the surface of a high-nickel ternary cathode material using a sol-gel wet process. Combined with a segmented sintering process, the inner LiAlO2 is formed into an amorphous or nanocrystalline-amorphous composite structure, the outer LATP is converted into crystalline lithium aluminum titanium phosphate, and a concentration gradient region with interdiffusion of elements is formed between the inner and outer layers. The cathode material prepared in this way has the advantages of good interface stability and high lithium-ion transport efficiency, and can take into account both high rate performance and cycle stability.
[0127] The above description describes some specific embodiments of this application, but in actual applications, the application should not be limited to these embodiments. For those skilled in the art, other modifications and alterations made based on the technical concept of this application should fall within the protection scope of this application.
Claims
1. A method for preparing a ternary cathode material, characterized in that, include: An aluminum source dispersion is added dropwise to a dispersion containing a high-nickel ternary cathode material and mixed. A lithium source and an aqueous solution containing a complexing agent are added and the pH is adjusted so that the aluminum source and the lithium source in the aluminum source dispersion undergo a hydrolysis-condensation reaction on the surface of the high-nickel ternary cathode material to form a LiAlO2 precursor gel coating the surface of the high-nickel ternary cathode material, thus obtaining the first precursor. A titanium source, phosphorus source, aluminum source, lithium source and solvent are mixed to form a lithium titanium aluminum phosphate precursor solution; The lithium titanium aluminum phosphate precursor solution is added dropwise to the first precursor, so that the lithium titanium aluminum phosphate precursor is deposited on the surface of the first precursor to obtain a composite precursor. The solvent in the composite precursor is evaporated to a wet gel state and then dried to obtain the dried composite precursor material. as well as, B2O3 flux is added to the dried composite precursor material and sintered to form an inner coating layer of amorphous LiAlO2 / or an inner coating layer of a composite of amorphous LiAlO2 and nanocrystalline LiAlO2 in the LiAlO2 precursor. At the same time, the lithium titanium aluminum phosphate precursor forms an outer coating layer of crystalline lithium titanium aluminum phosphate under the action of the B2O3 flux, thereby obtaining the cathode material.
2. The preparation method according to claim 1, characterized in that, During the sintering process, at the interface between the inner coating layer and the outer coating layer, at least one element between the amorphous LiAlO2 and the crystalline lithium titanium aluminum phosphate diffuses to form a concentration gradient region.
3. The preparation method according to claim 2, characterized in that, The step of adding B2O3 flux to the dried composite precursor material and sintering includes: B2O3 flux is added to the dried composite precursor material, and a first sintering is performed to form amorphous LiAlO2 on the surface of the high-nickel ternary cathode material, resulting in a first sintered product; and, The first sintered product is subjected to a second sintering, which causes the amorphous LiAlO2 to partially crystallize into nanocrystalline LiAlO2, forming an inner coating layer composed of amorphous LiAlO2 and nanocrystalline LiAlO2. At the same time, the lithium titanium aluminum phosphate precursor is converted into crystalline lithium titanium aluminum phosphate under the action of the B2O3 flux to form the outer coating layer. Under the second sintering conditions, at least one element between the amorphous LiAlO2 and the crystalline lithium titanium aluminum phosphate diffuses to form a concentration gradient region.
4. The preparation method according to claim 3, characterized in that, The sintering temperature for the first sintering is 350℃~450℃, and the time is 1h~3h; and / or, The secondary sintering temperature is 550℃~650℃, and the time is 2h~5h.
5. The preparation method according to claim 1, characterized in that, Based on the mass of the high-nickel ternary cathode material, the total addition amount of the inner coating layer and the outer coating layer is 0.5wt%~1.5wt%; and / or, The mass ratio of the inner coating layer to the outer coating layer is 2:1 to 5:
1.
6. The preparation method according to claim 1, characterized in that, The amount of B2O3 flux added is 0.5% to 3% of the mass of the lithium titanium aluminum phosphate precursor.
7. A ternary cathode material, characterized in that, The ternary cathode material includes a substrate and an inner coating layer and an outer coating layer covering the outer surface of the substrate; the substrate material includes a high-nickel ternary cathode material. The inner coating layer comprises amorphous LiAlO2 / or a composite structure of amorphous LiAlO2 and nanocrystalline LiAlO2; The outer coating layer contains crystalline lithium titanium aluminum phosphate.
8. The ternary cathode material according to claim 7, characterized in that, At the interface between the inner coating layer and the outer coating layer, at least one element between the amorphous LiAlO2 and the crystalline lithium titanium aluminum phosphate diffuses to form a concentration gradient region.
9. The ternary cathode material according to claim 7, characterized in that, The mass ratio of the inner coating layer to the outer coating layer is 2:1 to 5:1; and / or, The total coating amount of the inner coating layer and the outer coating layer is 0.5wt% to 1.5wt% of the mass of the matrix material.
10. An electrochemical device, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises a ternary positive electrode material as described in claim 9.